Structural studies of the haloalkane dehalogenase mutant (DhaA12) from Rhodococcus rhodochrous - Emmer, Jiří (Jihočeská univerzita, 2007)
Common crystallization procedures, X-ray diffraction method and crystallographic software to determine and refine the structure of haloalkane dehalogenase enzyme were used in this thesis.
Structural studies of the haloalkane dehalogenase mutant (DhaA12) from Rhodococcus rhodochrous
Keywords: X-ray crystallography; protein structure; DhaA; DhaA12 mutant; haloalkane dehalogenase; X-ray crystallography; protein structure; DhaA; DhaA12 mutant; haloalkane dehalogenase